2014
DOI: 10.3390/ijerph110909578
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach to Assess Exposure and Health-Risk from Polycyclic Aromatic Hydrocarbons (PAHs) in a Fastener Manufacturing Industry

Abstract: An integrated approach was developed to assess exposure and health-risk from polycyclic aromatic hydrocarbons (PAHs) contained in oil mists in a fastener manufacturing industry. One previously developed model and one new model were adopted for predicting oil mist exposure concentrations emitted from metal work fluid (MWF) and PAHs contained in MWF by using the fastener production rate (Pr) and cumulative fastener production rate (CPr) as predictors, respectively. By applying the annual Pr and CPr records to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…As shown in Supplement Table S1, abs λ=365 nm extracted by methanol displays good correlations with PAHs, OPAHs and nitrophenols, especially in winter (r > 0.89), which suggests that those species are important light absorption con-tributors for BrC in Xi'an. Huang et al (2018) found that PAHs and OPAHs in Xi'an accounted for, on average, 1.7 % of the overall absorption of methanol-soluble BrC, but their mass fraction in OC was only 0.35 %. A recent study reported that biomass burning also emitted nitroaromatic compounds, particularly nitrophenols, and accounted for 50 %-80 % of the total visible light absorption (> 400 nm) (Lin et al, 2017).…”
Section: Positive Matrix Factorization (Pmf) Source Apportionmentmentioning
confidence: 97%
See 1 more Smart Citation
“…As shown in Supplement Table S1, abs λ=365 nm extracted by methanol displays good correlations with PAHs, OPAHs and nitrophenols, especially in winter (r > 0.89), which suggests that those species are important light absorption con-tributors for BrC in Xi'an. Huang et al (2018) found that PAHs and OPAHs in Xi'an accounted for, on average, 1.7 % of the overall absorption of methanol-soluble BrC, but their mass fraction in OC was only 0.35 %. A recent study reported that biomass burning also emitted nitroaromatic compounds, particularly nitrophenols, and accounted for 50 %-80 % of the total visible light absorption (> 400 nm) (Lin et al, 2017).…”
Section: Positive Matrix Factorization (Pmf) Source Apportionmentmentioning
confidence: 97%
“…Many studies have been conducted on the BrC optical properties in China, but most of those were based on PM 2.5 and PM 10 sample collection and focused on the bulk aerosol optical properties with no information on the size distributions (Shen et al, 2017;Huang et al, 2018). Xi'an is a metropolitan city located in Guanzhong Basin of inland China, which is a typical semiarid region in East Asia and has been suffering from serious particle pollution due to the large emission of anthropogenic pollutants (Wu et al, 2018;Wang et al, 2016;Wu et al, 2019), especially intensive coal combustion and biomass burning in winter for house heating (Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Modeling made possible through distributions of probability amid uncertainties, provided by the BNs, to become appropriate to model the occupational risks, considering that it allows inference from hypotheses and on the relationship between risk factors. However, the risk is a changeable data when it regards to time (among other aspects), and modeling through the BNs satisfies this logic, as it stimulates stochastic processes (Englehardt et al, 2003;Hsu et al, 2014;Puncher et al, 2013;Xing et al, 2013).…”
Section: Stage Iii: Structural Proposal Of Application Of the Bnsmentioning
confidence: 99%
“…It is possible to highlight some results obtained with the application of the BNs in the analysis of occupational risk, namely: (1) In the transport sector, the results indicated that human factors were, among the direct factors, the most responsible for accidents, and among the indirect factors, the major influence was related to road conditions (Zhao et al, 2012); (2) In a study applied in the sector of industry, services and civil construction, it was shown that accidents at work had a strong direct relationship with the global set of hygiene and ergonomic factors, indicating that poor working conditions have a significant effect on health and safety in companies (García-Herrero et al, 2012a); (3) Intending to infer about the risks of occupational exposure to polycyclic aromatic hydrocarbons in the industrial sector, it was identified that prolonged exposure results in 74.4% chance of exceeding the acceptable risk of exposure (Hsu et al, 2014).…”
Section: Model Construction (Mc)mentioning
confidence: 99%
“…Beyond that, BrC also influence the atmospheric chemistry and human health. For example, BrC can shield polycyclic aromatic hydrocarbons (PAHs) from being oxidized, and thus substantially elevate lung cancer risk from PAHs (Hsu et al, 2014;Yan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%